Long-term monitoring of physical behavior reveals different cardiac responses to physical activity among subjects with and without chronic neck pain - Hallman, D.; Mathiassen, Svend; Lyskov, E. (Hindawi Publishing Corporation, 2015)
© 2015 David M. Hallman et al. Background. We determined the extent to which heart rate variability (HRV) responses to daily physical activity differ between subjects with and without chronic neck pain. Method. Twenty-nine subjects (13 women) with chronic neck pain and 27 age- and gender-matched healthy controls participated. Physical activity (accelerometry), HRV (heart rate monitor), and spatial location (Global Positioning System (GPS)) were recorded for 74 hours. GPS data were combined with a diary to identify periods of work and of leisure at home and elsewhere. Time- and frequency-domain HRV indices were calculated and stratified by period and activity type (lying/sitting, standing, or walking). ANCOVAs with multiple adjustments were used to disclose possible group differences in HRV. Results. The pain group showed a reduced HRV response to physical activity compared with controls (p =.001), according to the sympathetic-baroreceptor HRV index (LF/HF, ratio between low- and high-frequency power), even after adjustment for leisure time physical activity, work stress, sleep quality, mental health, and aerobic capacity (p =.02). The parasympathetic response to physical activity did not differ between groups. Conclusions. Relying on long-term monitoring of physical behavior and heart rate variability, we found an aberrant sympathetic-baroreceptor response to daily physical activity among subjects with chronic neck pain.